Social Capital and Self Efficacy of Pregnant Women - Kusumawati, Yuli; Supriyati, Supriyati (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2019)
Background: Mental health disorders, namely anxiety and depressive symptoms, are common in pregnant women due to physical and hormonal changes. Social support, family environment conditions and the neighboring social environment are components of social capital that contribute to the health of pregnant women. The Indonesia Healthy Family-Program Approach (HIP-FA) supports efforts to empower families to provide social support to pregnant women, thereby increasing self-efficacy in pregnancy that will lead to giving birth to healthy babies. This paper aims to describe the social capital and efficacy of pregnant women. Method: This study was a qualitative study that described social capital, empowerment, and self-efficacy of pregnant women during pregnancy. The article search was through PubMed, ProQuest, and Google Scholar databases. The keywords used to search the articles included: pregnant women, self-efficacy, social capital, and empowerment. The author examined and synthesized various kinds of literature that were closely related to social capital in providing self-efficacy for pregnant women. Results: Social capital affects health and is the main determinant of health. The important social capital is social support for pregnant women by empowering families to give better attention during pregnancy. A healthy Indonesian program with a family approach (HIP-FA) is organized in order to increase the government's attention in overcoming health problems by involving family directly in planning activities, monitoring and evaluation processes, so that the families understand well the health problems of pregnant women in their families and can provide social support in dealing with mental health disorders of pregnant women and increasing self-confidence to be mothers and parent. Conclusion: Social support is a social capital that can improve family empowerment by paying more attention to the health of pregnant women. Social capital in the form of family cohesion and family environment can improve the self-efficacy of pregnant women and prevent pregnancy complications to prepare for the birth of a healthy baby.